1987
DOI: 10.1177/028418518702800315
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Renal Tumor Embolization

Abstract: The medical reports of 113 patients operated upon for renal tumors were retrospectively reviewed to assess the value of preoperative embolization. Coils or ethanol were used preoperatively in 55 patients while 58 patients underwent nephrectomy without embolization. The tumors were staged according to the TNM and the Robson staging classification. TI and T2 tumors as well as T3 and T4 tumors were grouped together for statistical evaluation. There was no significant difference in intraoperative blood loss, opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreover, some studies have questioned the utility of preoperative RCC embolization, with no significant difference in intraoperative blood loss and operative time compared to PN without embolization. 24 However, embolization may become a useful tool to help the localization of the renal mass. Accordingly, our study aims to compare surgical and functional outcomes between off‐clamp RAPN with ICG tumour marking through preliminary selective RCC embolization and on‐clamp RAPN with IUS‐only identification.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have questioned the utility of preoperative RCC embolization, with no significant difference in intraoperative blood loss and operative time compared to PN without embolization. 24 However, embolization may become a useful tool to help the localization of the renal mass. Accordingly, our study aims to compare surgical and functional outcomes between off‐clamp RAPN with ICG tumour marking through preliminary selective RCC embolization and on‐clamp RAPN with IUS‐only identification.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to AMLs, safe injection of liquid sclerosants or embolic particles may require balloon occlusion or selective injection via a microcatheter. Renal artery embolization may also have a limited role in the palliative setting;[ 43 ] a recent report described radioembolization with yttrium-90 glass microspheres for palliative treatment of RCC in an 87-year-old woman with a 14.7 × 11.1 cm left renal mass, in which the mass remained stable in size and the patient reported decreased pain and hematuria during the first year following treatment. [ 44 ]…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
“…A subsequent series by Bakke et al [ 54 ] showed no difference in survival of patients with stage 4 renal cell carcinoma treated with embolisation/nephrectomy and embolisation alone. Fischedick et al [ 55 ] also found no survival benefit of embolisation prior to nephrectomy, and demonstrated no difference in peri-operative blood loss during nephrectomy between patients who received embolisation and those who did not. The failure of embolisation to reduce peri-operative blood loss was also seen in further series of 35 patients treated with embolisation with ethanol [ 56 ].…”
Section: Renal Cell Carcinomamentioning
confidence: 99%